Formation of a new model of election to the post of Commissioner for Human Rights in the Republic of Kazakhstan: problems and prospects - Issabekova, V.S.; Zalesny, J. (Bulletin of the Karaganda University “Law Series”, 2024)
This paper investigates the critical aspects of electing and nominating candidates for the role of Human Rights Commissioner in the Republic of Kazakhstan, providing an in-depth analysis of how the existing ombudsman framework functions within the nation. Furthermore, the research highlights the significance of adopting a method that allows for the nomination of multiple candidates during the ombudsman election process. Throughout this research, various legislative documents from CIS countries, national laws, and international legal frameworks that define the ombudsman’s legal status were meticulously examined. An examination of international practices in electing Human Rights Commissioners reveals that the methodologies employed in Kazakhstani legislation are somewhat restricted, suggesting that broadening the pool of eligible candidates could enhance the election process for a Human Rights Commissioner. The study suggests solutions for addressing deficiencies in the national legal framework concerning the election process by the competent authority. Recommendations are made for amending legislative provisions to embrace the fundamental democratic tenet of having alternatives and to align national laws with international norms.